2020
DOI: 10.1590/1678-4324-2020190084
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biological Effects of Marine Biosilica on a Tibial Bone Defect in Rats

Abstract: Research on biomaterials of natural origin has gained prominence in the literature. Above all, marine sponges, due to their architecture and structural components, present a promising potential for the engineering of bone tissue. In vitro studies demonstrate that a biosilica of marine sponges has osteogenic potential. However, in vivo works are needed to elucidate the interaction of biosilica (BS) and bone tissue. The objective of the study was to evaluate the morphological and chemical characteristics of BS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Transforming growth factor TGF-β has a positive effect for stimulating matrix protein synthesis and bone cell proliferation and thereby promotes bone remodeling . IHC stainings of TGF-β were used to investigate the factors responsible for promoting regeneration of the alveolar bone (Figure a2–f2,i).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transforming growth factor TGF-β has a positive effect for stimulating matrix protein synthesis and bone cell proliferation and thereby promotes bone remodeling . IHC stainings of TGF-β were used to investigate the factors responsible for promoting regeneration of the alveolar bone (Figure a2–f2,i).…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemistry (IHC) staining was carried out using TGF-β, IL-1, and TNF-α antibodies, following a standard protocol. Transforming growth factor TGF-β has a positive effect for stimulating matrix protein synthesis and bone cell proliferation and, thereby promotes bone remodeling . IHC stainings of TGF-β were used to investigate the factors for promoting regeneration of the alveolar bone.…”
Section: Methodsmentioning
confidence: 99%
“…Biosilica (BS) makes part of the inorganic skeleton of the marine sponges and it is formed by an enzymatic and silicatein-mediated reaction [9]. Some authors have extracted BS from sponges and demonstrated, through in vitro studies, evidences of BS osteogenic activity and ability to stimulate mineralization, upregulating the expression of genes related to bone cell differentiation and increase cell proliferation [10,11]. Also, marine spongin (SPG), with similar composition to vertebrate collagen, has been considered as a natural compound for tissue bioregeneration [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the marine biodiversity, marine sponges (the phylum Porifera) are one of the most promising sources of biological elements and molecules, with a vast therapeutic potential for a wide range of applications due mainly to the antitumor, antiviral, anti-in ammatory and antibiotic effects (SILVA et al, 2014). The inorganic part of the sponges, the glassy amorphous silica called biosilica (BS), and the organic part, the spongin-like collagen (SPG), have demonstrated bene cial effects on osteoblast and broblast cell proliferation and on the stimulation of tissue healing (DE ALMEIDA CRUZ et al, 2020;GABBAI-ARMELIN et al, 2018). Because silica ions are known as an important element to stimulate bone formation, BS (glassy amorphous silica-SiO 2 ) containing water and small amounts of Al, Ca, Cl, Cu, Fe, K, Na, S, and Zn (EHRLICH et al, 2010) has been demonstrated to have osteogenic effects in in vitro and in vivo studies (WANG et al, 2014).…”
Section: Introductionmentioning
confidence: 99%